(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the two years’ experience of myo-inositol use in women presented with polycystic ovarian syndrome at a tertiary care hospital. Study Design: Observational / cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology Unit-II, Chandka Medical College Hospital Larkana from January 2017 to December 2018. Materials and Methods: A total of 65 patients with polycystic ovarian syndrome were included. Detailed history was taken and myo-inositol was administrated to assess the outcomes i.e. conceiving of women, weight loss and menstrual regularity. Results: The mean age was 31.98+4.615 years. The results were 25 patients (38.5%) conceived after treatment, 15 (23.1%) had weight loss and menstrual regularity was noted in 20 patients (30.8%). Conclusion: The treatment of females with PCOS with myoinositol has showed considerable amount of improvements in terms of increasing fertilization along with omitting menstrual cycle irregularities and weight loss of the patients.